Synergistic effects from co-pyrolysis of low-rank coal and model components of microalgae biomass - Wu, Zhiqiang; Yang, Wangcai; Tian, Xueyu; Yang, Bolun (Energy conversion and management, 2017)
•Influence of three main compounds in spirulina and simulated spirulina on co-pyrolysis behavior was investigated.•Medium chain triglyceride showed positive synergistic effects with higher volatile yield.•Glycine and starch illustrated both positive and negative synergistic effects on char yield.•Non-additivity distribution of activation energy was solved by three model-free methods. Synergistic effects from co-pyrolysis microalgae biomass with low-rank coal were investigated in this work. Model compounds of three main component in microalgae algae (glycine, medium chain triglyceride and starch), spirulina and simulated spirulina were chosen to Shenfu bituminous pyrolysis process. Kinetic parameters were solved through isoconversional method, and scanning electron microscopy with energy dispersive spectroscopy were applied for characterizing the char samples. Results revealed synergistic effects occurred with different forms from co-pyrolysis of microalgae primary compounds and coal. Positive synergistic effects, which were defined as higher volatile yield than calculated value, were found in medium chain triglyceride and coal mixtures at all mass ratio. Whether positive or negative synergistic effects on products yield from glycine or starch blended with coal hinged on the temperature and mixing ratio. Both spirulina and simulated spirulina show optimal performance on volatile yields under 50wt.% mass ratio. Non-additivity phenomenon was observed on the distribution of average activation energy. Synergistic effects from co-pyrolysis of coal and microalgae biomass may attributes to the integrative action of the three model compounds.